Ensuring Teacher’s Job Satisfaction Through Distributed and Instructional Leadership of Chinese School Principals: Mediating Role of Reward, Motivation and Effectiveness - Xin, Zhao; Tahir, Suhaidah Binti (South Asian Journal of Social Sciences and Humanities, 2024)
Teacher performance and satisfaction is influenced through the organizational environment. Thus, this study explores the effectiveness of leadership styles in promoting teacher satisfaction, namely instructional leadership, and distributed leadership. The direct effects of instructional and distributed leadership on teacher’s job satisfaction along with the indirect effects through the mediation of reward, motivation and effectiveness were studied. The data was collected from 342 teachers employed in secondary schools of China, and the overall association among the factors was studied through the application of PLS-SEM. The findings of the study have indicated that instructional and distributed leadership styles are effective for curating the job satisfaction of teachers. Moreover, rewards, motivation, and job effectiveness were found to significantly mediate the association between leadership styles and job satisfaction. The results of the research study offer crucial implications for educational policies by demonstrating how job satisfaction among teachers can be enhanced through the implementation of appropriate leadership styles, emphasizing on reward, motivation, and effectiveness. The study suggests that development of teacher-focused policies and effective remuneration plans will lead towards satisfaction and therefore effective performance in the future.